Metode Identifikasi MaqÃ¢sid al-SharÃ®âah Muhammad TÃ¢hir b. âÃshÃ»r dalam Kitab MaqÃ¢sid al-SharÃ®âah al-IslÃ¢mÃ®yah - Aziz, Muhammad (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2014)
This article attempts to analyze how to know maqâsid al-shariâah in any statutes of shariâat with Muhammad Tâhir b. âÃshurâs perspective in the book of Maqâsid al-SharÃ®âah al-Islâmîya. This study concludes that the formula of turuq ithbât maqâsid al-shariâah in the perspective of Ibn âÃshur refers to three ways: first, through istiqrÃ¢â (inductive), be it istiqrÃ¢â on the known-rationale laws, or istiqrÃ¢â to the postulates of the law which has the same substantive rationale (mushtarak fî al-âillah), in which the existence of the rationale qualify as maqsûd al-ShÃ¢riâ; second, through the verses of the Quran which has the clarity of the arguments (wâdih al-dilâlah); and third, through the text of Sunnah mutawâtirah, either mutawâtir âamalÃ® or mutawâtir maânawÃ®.